Fatigue cracking characteristics of components stiffened with vertical ribs under eccentric loading in steel bridge deck. (June 2023) - Fang, Liang; Fu, Zhongqiu; Ji, Bohai; Wang, Yixun
Graphical abstract: Highlights: Clarify cracking features of components with vertical ribs under eccentric loading. Propose three-stage growth characteristics and its demarcations of CVR cracks. Suggest warning length for crack maintenance of components with vertical ribs. Provide controlling parameters for the repairing method of non-penetrating cracks. Abstract: The components in orthotropic steel decks are generally in an eccentrically loaded state for the nonuniformly distributed wheel loads. By conducting numerical simulation and fatigue tests of components stiffened by the vertical rib (CVR) with single butt weld, the propagation law of CVR cracks under eccentric loading were analyzed. By comparing with components stiffened by U-ribs (CUR), the difference of crack-growth characteristics between components with single and multi butt welds under eccentric loading was explored. The results show that CVR cracks will initiate at the eccentrically loaded side of the weld and propagate obliquely, but still perform the bilateral cracking mode as that under symmetric loading. The CUR and CVR cracks present the same three-stage characteristics of fast-slow-rapid growth and components will accelerate to failure in the third stage, which shall be avoided. The section-damage rate of CUR will be greatly relieved for the unilateral cracking under eccentric loading compared with that of bilateral cracking under symmetric loading, which delays the crack to enter the rapid-growth stage. Since there's little effect of eccentric loading on the demarcations of crack-growth stages in CVR, it is reasonable to take the demarcation 80 mm between the second and third crack-growth stages as the warning length for maintenance. The semi-elliptical CVR cracks will quickly penetrate base metal after extending to 75 % of thickness with the average ratio of crack depth to length being 0.09, which can be treated as the operation timing of maintenance methods for non-penetrating cracks.